Sebuah Potensi dan Tantangan Penggunaan Teknologi Penginderaan untuk Mendukung Pemberantasan Kelompok Kriminal Bersenjata di Papua - Andini Aprilia Ardhana; Sobar Sutisna; Trismadi Trismadi; Afpriyanto Afpriyanto; Fatmawati Fatmawati (CV. AFDIFAL MAJU BERKAH, 2024)
Papua, a resource-rich region in Indonesia, faces significant security challenges due to the presence of armed criminal groups (KKB). The eradication of KKB in this area requires advanced tools, among which sensing technology shows considerable promise. Sensing technologies, including satellites and drones, can offer precise and real-time data crucial for monitoring and responding to KKB activities. However, the effective deployment of these technologies is impeded by Papua's complex geographical terrain, extreme weather conditions, and inadequate infrastructure. This study aims to explore the potential of sensing technology in combating KKB by addressing these specific challenges and proposing strategies to optimize its use. Through a systematic literature review, the research identifies effective sensing methods and highlights the obstacles encountered in similar contexts. Findings suggest that adaptive technology development, increased resilience to weather conditions, and improvements in infrastructure are essential for maximizing the benefits of sensing technology. This research contributes to the development of effective strategies for eradicating KKB and enhancing security in Papua, emphasizing the need for coordinated efforts between government, research institutions, and the private sector to address the region's unique challenges.